Biosecurity-Based Architecture as a Surabaya Zoo Resilience Approach (International Journal of Architecture and Urbanism, 2023)
The Covid-19 pandemic has a direct impact on conservation institutions such as zoos. Although the Surabaya Zoo is now recovering along with the decline in cases, it requires a resilience strategy to face the threat of similar zoonotic diseases in the future. These threats have a negative impact not only on humans, but also on the welfare of the animals. This research looks at biosecurity as a form of risk management and problem prevention. Isolation, circulation systems, and waste treatment technology are the most important biosecurity components for zoos. The method begins by examining the biosecurity strategies implemented and planned by zoo associations around the world. The results of the analysis were then implemented at the Surabaya Zoo. It is necessary to analyze design elements in zoos such as entrances, circulations, and animal enclosures that still do not meet the concept of biosecurity. The study's findings include the implementation of a biosecurity strategy at the Surabaya Zoo from an architectural standpoint, a circulation system devoted to entry/exit access, and the provision of service areas that can be accommodated in one zone of Service Facilities. Also, noise mapping simulation shows that it is necessary to reduce noise in the facilities.